2020
DOI: 10.3390/biomedicines8120577
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HER2/neu Antibody Reduces Chemotherapy-Induced Ovarian Toxicity—From Bench to Bedside

Abstract: Background: Trastuzumab, a humanized anti-human epidermal growth factor receptor 2 (HER2/neu) antibody, is considered a standard treatment in addition to chemotherapy in the adjuvant setting for HER2/neu-positive breast cancer, yet its impact on fertility and ovarian reserve remains obscure. We aimed to study the effect of anti-HER2/neu on chemotherapy-induced ovarian toxicity in both clinical and preclinical settings. Methods: We prospectively enrolled breast cancer patients below the age of 42 years who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Evidence from the adjuvant paclitaxel and trastuzumab (APT) clinical trial, a single-arm phase 2 study of 12 weeks of adjuvant paclitaxel and trastuzumab followed by 9 months of trastuzumab monotherapy, indicated that amenorrhea rates among premenopausal women treated with adjuvant non-alkylating paclitaxel and trastuzumab for early-stage breast cancer appeared lower than those historically seen with standard alkylating-based breast cancer regimens (28% in this study vs approximately 50% in earlier studies) ( Ruddy et al 2015 ). These findings were recapitulated in a separate study examining breast cancer patients treated with chemotherapy with or without trastuzumab, and while AMH levels declined to undetectable levels by 6 months post-treatment, 57.1% of the HER2-positive cohort showed a degree of recovery of AMH to detectable levels by 12 months post-treatment, compared to 36.8% in the negative cohort ( Levi et al 2020 ). Further exploration in a prepubertal mouse model injected with cyclophosphamide or paclitaxel with or without trastuzumab, or saline, and sacrificed 1 week or 3 months later, showed that trastuzumab significantly reduced the vascular damage of both cyclophosphamide and paclitaxel, with these ovaries exhibiting less apoptosis (determined using qualitative TUNEL staining and quantitative CD34+ blood vessel analysis) and a higher ovarian reserve (assessed via ovarian weight, serum AMH, and ovarian follicle stage proportions) following treatment ( Levi et al 2020 ).…”
Section: Egfr/her Inhibitorsmentioning
confidence: 68%
See 1 more Smart Citation
“…Evidence from the adjuvant paclitaxel and trastuzumab (APT) clinical trial, a single-arm phase 2 study of 12 weeks of adjuvant paclitaxel and trastuzumab followed by 9 months of trastuzumab monotherapy, indicated that amenorrhea rates among premenopausal women treated with adjuvant non-alkylating paclitaxel and trastuzumab for early-stage breast cancer appeared lower than those historically seen with standard alkylating-based breast cancer regimens (28% in this study vs approximately 50% in earlier studies) ( Ruddy et al 2015 ). These findings were recapitulated in a separate study examining breast cancer patients treated with chemotherapy with or without trastuzumab, and while AMH levels declined to undetectable levels by 6 months post-treatment, 57.1% of the HER2-positive cohort showed a degree of recovery of AMH to detectable levels by 12 months post-treatment, compared to 36.8% in the negative cohort ( Levi et al 2020 ). Further exploration in a prepubertal mouse model injected with cyclophosphamide or paclitaxel with or without trastuzumab, or saline, and sacrificed 1 week or 3 months later, showed that trastuzumab significantly reduced the vascular damage of both cyclophosphamide and paclitaxel, with these ovaries exhibiting less apoptosis (determined using qualitative TUNEL staining and quantitative CD34+ blood vessel analysis) and a higher ovarian reserve (assessed via ovarian weight, serum AMH, and ovarian follicle stage proportions) following treatment ( Levi et al 2020 ).…”
Section: Egfr/her Inhibitorsmentioning
confidence: 68%
“…These findings were recapitulated in a separate study examining breast cancer patients treated with chemotherapy with or without trastuzumab, and while AMH levels declined to undetectable levels by 6 months post-treatment, 57.1% of the HER2-positive cohort showed a degree of recovery of AMH to detectable levels by 12 months post-treatment, compared to 36.8% in the negative cohort ( Levi et al 2020 ). Further exploration in a prepubertal mouse model injected with cyclophosphamide or paclitaxel with or without trastuzumab, or saline, and sacrificed 1 week or 3 months later, showed that trastuzumab significantly reduced the vascular damage of both cyclophosphamide and paclitaxel, with these ovaries exhibiting less apoptosis (determined using qualitative TUNEL staining and quantitative CD34+ blood vessel analysis) and a higher ovarian reserve (assessed via ovarian weight, serum AMH, and ovarian follicle stage proportions) following treatment ( Levi et al 2020 ). Collectively, these studies suggest that EGFR inhibitors may be safer than standard chemotherapy treatments, with no lasting effects on ovarian function and fertility; however, additional long-term follow-up studies are required to examine oocyte quality and subsequent offspring health.…”
Section: Egfr/her Inhibitorsmentioning
confidence: 68%
“…We have validated this method in previous studies. 21 23 The use of TUNEL and its range as apoptotic index is familiar to us from a number of previous studies. In our extensive experience, even with very testicular-toxic agents (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Prior exploratory and mostly descriptive analyses of trials investigating different anti‐HER2 agents have reported the risk of gonadotoxicity with trastuzumab, lapatinib and T‐DM1. The main results of these analyses have shown that adding trastuzumab to chemotherapy does not appear to increase the risk of post‐treatment amenorrhoea, 6–8 without differences when using trastuzumab alone, lapatinib alone or their combination 9 . Even if these analyses suggest that trastuzumab and/or lapatinib have no apparent gonadotoxicity, it should be highlighted that most of the patients included in these studies had received prior anthracycline‐ and cyclophosphamide‐based chemotherapy.…”
Section: Figurementioning
confidence: 99%